A RESEARCH ON PROFESSIONALISM OF IMAM-HATIP HIGH SCHOOL TEACHERS - Abdulkadir ÇEKİN (Fırat University, 2019)
One of the basic elements of the process of education is a teacher. Teacher is the one who interact with students, manage lessons, measure and evaluate lesson process. In this regard, the teacher's professional qualities affect the quality of instruction. Teachers are faced with this multi-tasking structure to them requires a professional approach their profession. Professionalism requires that getting all the necessary qualifications for a job. Teaching is one of the leading professional occupations. The aim of this research is to reveal that the professionalism approaches of imam-hatip high school teachers, effective and ineffective factors about their professionalism. For this purpose, it has been analyzed that the professionalization of teachers and provider factors affecting professionalism of the teachers with such a thing as influential actors. The sample of the survey is 70 imam-hatip high school vocational courses teachers. In the research, ‘Teacher Professionalism Inventory’ and ‘Personal Information Form’ were used. In the analysis of data, it was benefited from ‘One Way Analysis of Variance’, ‘Independent Simple t-Test’ and ‘SPSS 16.0’ in order to analyses data. According to the results of the research it was found that (1) the vast majority of imam-hatip high school teachers (92,9%) believes that they have the professional qualities. (2) The school management (X = 4.28), the teacher's personality (X = 4.02) and the government's education policy (X = 3.66) are the foremost important factors, on the other hand, occupational career (X = 3.28) and the salary and wages (X = 3.00) are unimportant factors on the teachers professionalism.